Soluble Dipeptidyl Peptidase-4 Induces Fibroblast Activation Through Proteinase-Activated Receptor-2 - Lee, Shih-Yi; Wu, Shao-Tung; Liang, Yao-Jen; Su, Ming-Jai; Huang, Cheng-Wei; Jao, Yu-Hsuan; Ku, Hui-Chun (Frontiers in Pharmacology, 2020)
Human fibrotic diseases are a major global health problem. Fibroblasts are the chief secretory cells of the extracellular matrix (ECM) responsible for the basal deposition and degradation of the ECM under normal conditions. During stress, fibroblasts undergo continuous activation, which is defined as the differentiation of fibroblasts into myofibroblasts, a cell type with an elevated capacity for secreting ECM proteins. Dipeptidyl peptidase-4 (DPP4) inhibitors are being developed for treating diabetes. DPP4 is a ubiquitously expressed transmembrane glycoprotein and exerts effects that are both dependent and independent of its enzymatic activity. Shedding of DPP4 from different tissues into circulation appears to be involved in diseases. The mechanism underlying soluble DPP4-induced fibrosis has not been clearly determined. The effect of DPP4 on fibroblasts was evaluated by measuring the expression of fibrotic markers. Soluble DPP4 stimulated the activation of fibroblasts in a dose-dependent manner by activating nuclear factor-kappa B (NF-κB) and suppressor of mothers against decapentaplegic (SMAD) signaling. Blocking proteinase-activated receptor-2 (PAR2) abrogated the DPP4-induced activation of NF-κB and SMAD, and expression of fibrosis-associated proteins in fibroblasts. Linagliptin, a clinical available DPP4 inhibitor, was shown to abrogate the soluble DPP4-induced expression of fibrotic protein. This study demonstrated a novel role of soluble DPP4, which activated NF-κB and SMAD signaling through PAR2, leading to the activation of fibroblasts. Our data extend the current view of soluble DPP4. Elevated levels of circulating soluble DPP4 may contribute to one of the mediators that induce fibrosis in patients.